Effect of Mn-doping on the low temperature magnetic phase transitions of BiFeO3 - Kumar A.; Singh P.; Choudhary R.J.; Pandey D. (My University, 2025)
In the present work, we have carried out a comparative study of the low temperature phase transitions using dc magnetization (M (T)) and ac susceptibility (χ (ω, T)) measurements on undoped and 0.3 wt% MnO2 doped BiFeO3 samples in the 2–300 K temperature range. It is shown that MnO2 doping increases the resistivity and decreases the dielectric loss as a result of reduced oxygen vacancy concentration as confirmed by iodometry and x-ray photoelectron spectroscopy (XPS) studies. A comparative study of the dc M (T) and ac χ (ω, T) results on two types of samples reveal that the transitions around 25 K, 110 to 150 K and 260 K are intrinsic to BiFeO3. The widely reported transition at 50 K is argued to be defect induced, as it is absent in the doped samples. We also show that the spin-glass transition temperature (TSG) ∼20 K, determined from an analysis of χ (ω, T), is less than the spin-glass freezing temperature (Tf) ∼25 K in marked contrast to TSG > Tf reported by earlier workers. © 2020 Elsevier B.V.